Pengaruh Kinerja Keuangan Perusahaan Terhadap Harga Saham Pada Perusahaan Rokok Yang Terdaftar Di BEI Tahun 2013-2015 - Agustina, Lia, Drs. Sujadi, M.M (2017)
This study aims to determine the effect of the financial performance of the stock price of cigarettes companies listed in Indonesia Stock Exchange (BEI) in 2013-2015, either partially or simultaneously. Financial ratios studied include: return on assets (ROA), earnings per share (EPS), the price earnings ratio (PER). The population in this study is a cigarette company listed on the Indonesia Stock Exchange (BEI) in 2013-2015. Samples are four cigarette companies acquired by purposive sampling. Data was analyzed using multiple regression analysis techniques. The results showed that partially ROA positive and significant impact on stock prices, EPS positive and significant impact on stock prices, and PER positive and significant impact on stock prices. Simultaneously ROA, EPS, and PER affect stock prices. The results of this study are relevant or similar to the results of previous studies.